Gaya Hidup, Literasi Keuangan Syariah, dan Pembelian Impulsif Konsumen Muslim Deli Serdang - T. Fadlanil Muflih (MAN 4 Kota Pekanbaru, 2026)
This study examines the role of lifestyle and Islamic financial literacy in shaping impulsive buying behavior among Muslim consumers in Deli Serdang. The rapid growth of digital commerce has intensified unplanned purchases that potentially contradict Islamic consumption ethics. A quantitative explanatory design was employed with a survey of 200 Muslim consumers selected through purposive sampling. Data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. This study extends previous research by examining Muslim consumers in an urban–semi urban community rather than student samples commonly used in earlier studies. The findings reveal that lifestyle has a positive and significant effect on impulsive buying, while Islamic financial literacy has a negative and significant effect. Simultaneously, both variables significantly explain impulsive buying behavior with a moderate coefficient of determination. The study implies that strengthening Islamic financial literacy and promoting moderate lifestyles are essential to develop responsible Muslim consumer behavior in the digital economy.